Development of Academic Information System Mobile Application Prototype at SD Inpres Touiu, Rote - Vienda Miccela Seldry; Hamidillah Ajie; Murien Nugraheni (Universitas Pendidikan Indonesia, 2024)
In era society 5.0, where technology is generally a supporting factor in many ways, it turns out that there are still some aspects that have not taken advantage of existing technology. For example, Inpres Touiu Elementary School, Rote in providing information is still done manually, such as the recipient of the information coming directly to the location of the information or information being delivered by the school to the recipient of the information such as the teacher coming directly to the house of each student. The purpose of this research is to produce a prototype of an Android-Based School Academic Information System with a Case Study of SD Inpres Touiu, Rote which is useful in providing an information system design in the form of a front-end, so that in the future it can be redeveloped into a real android application. The results of the development in the form of a high-fidelity prototype using the Flutter framework with the Waterfall Method resulted in the SIKALA prototype being tested for Usability Testing using Black box testing and the Think-aloud method. The results of the test got 94% good response and 100% overall task success.